Faktor-faktor yang memengaruhi harga saham sektor consumer non-cyclicals - Haryadi, Richard; Winarto, Jacinta (Jurnal Manajemen Maranatha, 2024)
Economic conditions are full of uncertainty, which can make non-cyclicals consumer (JKNONCYC) sector stocks benefit. Research was conducted to determine the effect of GPM, EPS, ROE, DER, and innovation on stock prices in JKNONCYC sector stocks listed on the Indonesia Stock Exchange (IDX) in 2018-2022, so that companies can make use of the situation. The population in this study was 122 companies, while the sample was 13 companies selected using purposive sampling method. The analysis technique used is panel data regression analysis with the fixed effect model method. The result showed that partially GPM and DER had no effect on stock prices, EPS and innovation had a positive effect on stock prices, while ROE had a negative effect on stock prices. Simultaneously, GPM, EPS, ROE, DER, and innovation affect stock prices by 98.67 percent. Companies can increase stock prices by paying attention to the level of EPS, ROE, and innovation, so that investors are interested in investing.